Polycarbonyl organic electrode material containing naphthalimide and application of polycarbonyl organic electrode material in metal ion battery

By developing polycarbonyl organic electrode materials containing naphthalimide, the problems of low specific capacity and short cycle life of zinc-ion batteries and lithium-ion batteries have been solved, and battery performance of high specific capacity, long cycle life and high rate performance have been achieved. And the materials are environmentally friendly.

CN119350331AActive Publication Date: 2025-01-24CHANGZHOU UNIV

Patent Information

Application Number
CN202411415291.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Existing zinc-ion batteries and lithium-ion batteries have problems with low specific capacity, short cycle life and difficulty in developing high-voltage aqueous zinc batteries, and lack high-performance organic electrode materials that can be applied to zinc-ion batteries and lithium-ion batteries at the same time.

Method used

The development of a multivarbing -based organic electrode material containing a gelide is developed. This material introduces the pyride amine and benzal. And cycle stability.

Benefits of technology

The high specific capacity, long cycle life and high rate performance of zinc-ion batteries and lithium-ion batteries are achieved, and the raw materials are easily available, the synthesis is simple, the yield is high, and they are environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350331A_ABST
    Figure CN119350331A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal ion battery electrode materials, and particularly discloses a naphthalimide-containing polycarbonyl organic electrode material and application thereof in a metal ion battery. The multi-carbonyl organic electrode material is obtained by reacting 1, 4, 5, 8-naphthalene tetracarboxylic anhydride with 2, 5-dimethoxyaniline and then oxidizing. When the polycarbonyl organic compound is used as an electrode material of a zinc ion battery, the specific capacity of 1100mAh / g can be realized, the specific capacity of 250mAh / g can be realized under the conditions of high voltage of 2.0 V and current density of 1A / g, and the total number of stable cycles exceeds 4000. In addition, when the polycarbonyl compound is used as an electrode material of a lithium ion battery, the specific capacity as high as 651mAh / g and excellent stability can be realized. The naphthalimide-containing multi-carbonyl organic electrode material provided by the invention has a relatively good application prospect in a metal ion battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal ion battery electrode materials, in particular to a polycarbonyl organic electrode material containing naphthalene imide and application thereof in metal ion batteries. Background Art

[0002] The development of high-performance, long-life, low-cost secondary batteries plays an important role in solving the global energy crisis and environmental pollution problems, and is an important research direction in the current new energy field. In the field of secondary battery research, lithium-ion batteries have been widely studied due to their advantages such as high energy density, long cycle life and no memory effect, and are widely used in electric vehicles, smart phones and other fields. However, the current lithium battery capacity on the market is about 100-300mAh / g. With the rapid development of the market, it is difficult to meet the demand for high capacity. It is urgent to further develop high-capacity, long-life, low-cost and highly safe lithium-ion batteries.

[0003] In addition, zinc-ion batteries, as a new type of secondary battery, have also received extensive attention and research due to their low cost, high safety and good environmental protection. At present, the performance of zinc-ion batteries has made certain progress, but there is still a certain gap compared with lithium-ion batteries, mainly manifested in low specific capacity, usually between 50-150mAh / g, such as zinc-manganese batteries: specific capacity is about 50-80mAh / g, and the cycle life is short. Moreover, for aqueous zinc-ion batteries, it is difficult to develop high-voltage aqueous zinc batteries due to the decomposition of water. In short, the development of aqueous zinc batteries with high voltage, high capacity and excellent cycle stability still faces great challenges.

[0004] In particular, organic materials with excellent redox activity are easy to obtain and cheap, and their structures are rich and adjustable. As electrode active materials, they can also present high specific capacity. In view of this, it is of great significance to develop cheap and high-performance organic electrode materials for application in metal ion batteries. At present, some excellent performance zinc ion organic electrode materials (Angewandte Chemie, 2022, 134 (51): e202214244; Science advances, 2018, 4 (3): eaao1761.) and lithium ion organic electrode materials (CN 110429279A, Materials Today 50 (2021): 170-198, ACS Applied Polymer Materials 5.11 (2023): 9128-9137.) have been developed, but the specific capacity, long cycle performance and rate performance of related organic electrode materials still need to be further improved. Moreover, few high-performance organic electrode materials that can be applied to zinc ion batteries and lithium ion batteries have been developed. Summary of the invention

[0005] In view of the above problems, the present invention has developed an organic electrode material with multiple active sites, and has a low solubility in both organic solvents and water, and has applied it to zinc ion batteries and lithium ion batteries, which can achieve high specific capacity, long cycle life and high rate performance.

[0006] The polycarbonyl organic electrode material containing naphthaleneimide, which can be applied to metal zinc ion batteries and lithium ion batteries, provided by the present invention, introduces naphthaleneimide and benzoquinone units with redox activity, and utilizes multiple active sites in the structure to achieve high specific capacity. Moreover, it forms a large planar structure, which can reduce the solubility in water or organic solvents, and will be beneficial for achieving stable cycle performance and excellent rate performance. The raw materials of this simple organic electrode material are easy to obtain, the synthesis is simple, the yield is high, and it can achieve higher energy density, good cycle stability and excellent comprehensive electrochemical performance in zinc ion battery and lithium ion battery systems, and has good application prospects.

[0007] The polycarbonyl organic electrode material containing naphthalene imide provided by the present invention has a structural formula as shown in Formula D1:

[0008]

[0009] The present invention also provides a method for preparing the above-mentioned polycarbonyl organic electrode material containing naphthaleneimide: 1,4,5,8-naphthalenetetracarboxylic anhydride and 2,5-dimethoxyaniline are dissolved in DMF (N,N-dimethylformamide), heated to 100-150°C, stirred and refluxed for reaction for 10 hours, after the reaction is completed, washed with DMF and ethanol for multiple times, and dried to obtain a product precursor, the precursor and ammonium cerium nitrate are dissolved in a mixed solution of deionized water and acetonitrile (volume ratio of 2:8), stirred and reacted at room temperature for 2 hours, after the reaction is completed, washed with ethanol and deionized water for multiple times, and dried to obtain the target product D1.

[0010] The reaction formula for preparing polycarbonyl organic electrode materials is as follows:

[0011]

[0012] Wherein, the molar ratio of 1,4,5,8-naphthalenetetracarboxylic anhydride to 2,5-dimethoxyaniline is 1:2 to 2.5.

[0013] The amount ratio of the precursor to the ammonium cerium nitrate substance is 1:4-5.

[0014] The polycarbonyl organic electrode material of the present invention is used for preparing the positive electrode of zinc ion battery. When used for the positive electrode of zinc ion battery, the current collector can be graphite paper, and the electrolyte can be sulfuric acid, zinc sulfate or zinc sulfonate.

[0015] The method for preparing the battery electrode material used in zinc ion batteries is as follows:

[0016] D1 material, PVDF, acetylene black and / or carbon nanotubes are mixed and ground together in a certain mass ratio. After being evenly mixed, an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added and ground into a paste slurry, which is coated on graphite paper and vacuum dried at 80°C for 12 hours to obtain a battery electrode sheet (D1 composite material); the composite material is used as a positive electrode, Whatman glass fiber isolation membrane GF / D is used as a battery separator, sulfuric acid, zinc sulfate and zinc sulfonate are used as electrolytes respectively, a zinc sheet is used as a negative electrode, and a button battery is assembled using a conventional process.

[0017] The polycarbonyl organic electrode material of the present invention can also be used to prepare the positive electrode of a lithium ion battery. The current collector used to prepare the positive electrode of the lithium ion battery is aluminum foil, and the electrolyte is 1 mol / L lithium bis(trifluoromethylsulfonyl)imide.

[0018] The method for preparing the battery electrode material used in preparing lithium-ion batteries is as follows:

[0019] The product D1, acetylene black and binder polyvinylidene fluoride (PVDF) are mixed in a certain mass ratio, ground and mixed into a slurry with N-methylpyrrolidone (NMP) as a solvent, and then evenly coated on the current collector aluminum foil, and then dried in a vacuum drying oven at 80°C to obtain a battery electrode (D1 composite material), and the dried electrode is cut into a round piece with a diameter of 12 mm; a metal lithium sheet is used as the negative electrode, the D1 composite material is used as the positive electrode, the separator is Ce1grad 2550, and the electrolyte uses 1 mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI), and the electrolyte in the electrolyte is lithium bistrifluoromethanesulfonyl imide; the electrolyte solvent is a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME), and the battery is assembled in a glove box filled with argon protection.

[0020] The advantages of the present invention are: the polycarbonyl organic electrode material of the present invention can be used as a multifunctional electrode material to construct a zinc ion battery with a specific capacity of up to 1100mAh / g and a lithium ion battery with a specific capacity of up to 651mAh / g; in particular, the zinc ion battery can achieve a long-life cycle at a high voltage of 2.0V. The polycarbonyl organic electrode material has low solubility in water and organic solvents, has good structural stability during the charge and discharge process, and exhibits good rate performance; the polycarbonyl organic electrode material raw materials are easy to obtain, easy to synthesize, high in yield, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Multiple constant current charge and discharge curves of a zinc ion battery using Example D1 as the electrode active material at 50 mA / g, wherein the values ​​1, 3, 30, and 100 correspond to different cycle numbers, respectively.

[0022] Figure 2 It is the long cycle specific capacity of the zinc ion battery using Example D1 as the electrode active material at 50 mA / g.

[0023] Figure 3 The constant current charge and discharge capacity of the zinc ion battery using Example D1 as the electrode active material at different current densities.

[0024] Figure 4 The long cycle of the zinc ion battery using Example D1 as the electrode active material at different cut-off voltages at a current density of 1000 mA / g.

[0025] Figure 5 The cycle specific capacity of the zinc ion battery using Example D1 as the electrode active material at a cut-off voltage of 0.2-1.6V, 0.15-1.8V, 0.15-1.9V, and 0.1-2.0V at a current density of 1A / g.

[0026] Figure 6 The figure is the cycle curve of the zinc ion battery using Example D1 as the electrode active material at a high cut-off voltage of 2V.

[0027] Figure 7 It is the long cycle specific capacity of the lithium ion battery using Example D1 as the electrode active material at 50 mA / g. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be noted that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] Example 1

[0030] A method for preparing a zinc ion battery electrode material comprises the following steps:

[0031] Take (1g) 3.73mmol of 4,5,8-naphthalenetetracarboxylic anhydride and (1.2g) 7.84mmol of 2,5-dimethoxyaniline and dissolve them in DMF (N,N-dimethylformamide), reflux at 140°C for 10h, wash with DMF and then with ethanol three times after the reaction, dry to obtain 1.55g of product precursor, take 1g (1.857mmol) of the precursor and dissolve it in 15mL of a mixed solvent of deionized water and acetonitrile, add 5.09g (9.285mmol) of ammonium cerium nitrate and mix (wherein, the mass ratio of the precursor to ammonium cerium nitrate is 1:5, and the volume ratio of water to acetonitrile is 2:8), stir at room temperature for 2h, after the reaction is completed, wash with deionized water and then with ethanol until the washing liquid is colorless, dry to obtain the target product D1, and the yield is 91%.

[0032] Take 50 mg of product D1, 40 mg of acetylene black and 10 mg of PVDF (a total of 100 mg (mass ratio of 5:4:1)) and grind them together. After mixing evenly, add 1 ml of NMP and grind them into a paste slurry. Evenly apply it on graphite paper at a density of 1 mg / cm 2 Then put it in an oven at 80℃ for 12 hours, and cut the dried electrode into a 12mm diameter disc. The electrode is used as the positive electrode, Whatman glass fiber separator GF / D is used as the diaphragm, 0.5M H2SO4 is used as the electrolyte, and the zinc sheet is used as the negative electrode. The button battery is assembled using conventional technology.

[0033] The button cell assembled according to the method is subjected to charge and discharge cycle test in the voltage range of 0.1-1.6V. The curve (such as Figure 1 , Figure 2 ), the test results show that the electrode material can achieve a specific capacity of up to 1100mAh / g (such as Figure 1 , Figure 2 ).

[0034] Example 2

[0035] Preparation method of zinc ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0036] Preparation of zinc ion battery electrode materials and testing of their electrochemical performance;

[0037] Take 50 mg of D1, 30 mg of acetylene black, 10 mg of PVDF and 10 mg of carbon nanotubes (total 100 mg, mass ratio 5:3:1:1) and grind them together. After mixing evenly, add 1 ml of NMP and grind into a uniform slurry. Apply it on graphite paper at a density of 1 mg / cm 2 Then put it in an oven at 80℃ for 12 hours, and cut the dried electrode into a 12mm diameter disc. Use the electrode as the positive electrode, Whatman glass fiber separator GF / D as the diaphragm, 0.3M zinc sulfonate as the electrolyte, zinc sheet as the negative electrode, and assemble the button battery using conventional technology.

[0038] When the battery voltage is tested at a rate within the range of 0.2-1.6V, it is found that when the current density is 50mA / g, the reversible discharge capacity of the battery is 210mAh / g. As the battery operating current reaches 100mA / g, the reversible discharge capacity of the battery reaches 190mAh / g. When the current density reaches 200mA / g, the reversible discharge capacity of the battery is 180mAh / g. When the battery operating current reaches 300mA / g, the reversible discharge capacity of the battery can still reach 170mAh / g. When the current density reaches 400mA / g, the reversible discharge capacity of the battery is 160mAh / g. When the battery operating current reaches 500mA / g, the reversible discharge capacity of the battery can still reach 150mAh / g. When the current density reaches 1000mA / g, the reversible discharge capacity of the battery is 125mAh / g. When the current density reaches 2000mA / g, the reversible discharge capacity of the battery is 80mAh / g. Finally, when the current density was adjusted back to 50 mA / g, the capacity returned to 215 mAh / g, indicating that the electrode material has good rate performance (such as Figure 3 ).

[0039] The battery was charged and discharged with a high current, the current density was set to 1A / g, the cut-off voltage was set to 1.6V, 1.8V, 1.9V, 2.0V, and the long cycle was more than 4000 cycles (such as Figure 4 ).

[0040] At different cut-off voltages of 1.6V, 1.8V, 1.9V, and 2.0V, and a current density of 1A / g, the charge and discharge curves show that the greater the cut-off voltage, the greater the battery specific capacity (e.g. Figure 5 ). At a cut-off voltage of 2V, a current density of 1A / g was achieved to achieve a specific capacity of 250mAh / g (e.g. Figure 6 ).

[0041] Example 3

[0042] The preparation method of zinc ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0043] A zinc ion battery, made of the zinc ion electrode material, and its electrochemical performance test;

[0044] The assembly method and active material ratio are the same as those in Example 2, and 0.5M H2SO4 is used as the electrolyte.

[0045] The battery made in this example was tested for its charge-discharge capacity and cycle characteristics. After 100 cycles, the specific capacity can be maintained at about 190 mAh / g, and the coulombic efficiency is always above 90%.

[0046] Example 4

[0047] The preparation method of zinc ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0048] A zinc ion battery, made of the zinc ion electrode material, and its electrochemical performance test;

[0049] The assembly method and active material ratio are the same as those in Example 2, and 1.5M H2SO4 is used as the electrolyte.

[0050] The battery made in this example was tested for its charge-discharge capacity and cycle characteristics. After 100 cycles, the specific capacity can be maintained at about 180 mAh / g, and the coulombic efficiency is always above 90%.

[0051] Example 5

[0052] The preparation method of zinc ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0053] A zinc ion battery, made of the zinc ion electrode material, and its electrochemical performance test;

[0054] The assembly method and active material ratio are the same as those in Example 2, and 2M zinc sulfonate is used as the electrolyte.

[0055] The battery made in this example was tested for its charge-discharge capacity and cycle characteristics. After 100 cycles, the specific capacity can be maintained at about 110 mAh / g, and the coulombic efficiency is always above 85%.

[0056] Example 6

[0057] The preparation method of zinc ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0058] A zinc ion battery, made of the zinc ion electrode material, and its electrochemical performance test;

[0059] The assembly method and active ingredient ratio are the same as those in Example 2, and 3M zinc sulfate is used as the electrolyte.

[0060] The battery made in this example was tested for its charge-discharge capacity and cycle characteristics. After 100 cycles, the specific capacity can be maintained at about 180 mAh / g, and the coulombic efficiency is always above 80%.

[0061] Example 7

[0062] The preparation method of lithium ion battery electrode material D1 is synthesized according to the preparation steps of Example 1;

[0063] Lithium-ion battery, made of the lithium-ion electrode material, and its electrochemical performance test;

[0064] Take 50 mg of product D1, 40 mg of acetylene black and 10 mg of binder polyvinylidene fluoride (PVDF) to mix, totaling 100 mg (mass ratio of 5:4:1), use 0.5 ml of N-methylpyrrolidone (NMP) as solvent, grind and mix into slurry, and evenly coat it on the current collector aluminum foil at 1 mg / cm 2 Then, it was dried in a vacuum drying oven at a temperature of 80°C for 12 hours, and the dried electrode was cut into a disc with a diameter of 12 mm; a metal lithium sheet was used as the negative electrode, a D1 composite material was used as the positive electrode, and Ce1grad2550 provided by Cluder was used as the diaphragm. The electrolyte used was 1 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI), and the electrolyte in the electrolyte was lithium bistrifluoromethylsulfonyl imide; the electrolyte solvent was a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME), and the volume ratio was 1:1. The conventional battery assembly process was used to assemble the battery in a glove box filled with argon protection.

[0065] The battery made in this example was tested for its charge-discharge capacity and cycle characteristics. After 275 cycles, the specific capacity gradually increased from the original 120mAh / g. At 384 cycles, the capacity reached 651mAh / g, and the coulombic efficiency was always above 80% ( Figure 7 ).

Claims

1. A polycarbonyl organic electrode material containing naphthalene imide, characterized in that: The structural formula of the electrode material is shown in Formula D1:

2. The polycarbonyl organic electrode material containing naphthalene imide according to claim 1, characterized in that: The preparation method of the electrode material comprises the following steps: dissolving 1,4,5,8-naphthalenetetracarboxylic anhydride and 2,5-dimethoxyaniline in N,N-dimethylformamide, heating and refluxing the mixture, washing the mixture with N,N-dimethylformamide and ethanol, and drying the mixture to obtain a precursor; mixing the precursor with a cerium ammonium nitrate solution dissolved in a mixed solvent of deionized water and acetonitrile, stirring the mixture at room temperature for 2 hours, washing the mixture with ethanol and deionized water, and drying the mixture to obtain the target product D1.

3. The polycarbonyl organic electrode material containing naphthalene imide according to claim 2, characterized in that: The molar ratio of 1,4,5,8-naphthalenetetracarboxylic anhydride to 2,5-dimethoxyaniline is 1:2-2.5, and the molar ratio of the precursor to ammonium cerium nitrate is 1:4-5.

4. The polycarbonyl organic electrode material containing naphthalene imide according to claim 2, characterized in that: The heating reflux reaction is carried out by stirring the reaction at 100-150° C. for 10 hours.

5. An application of the polycarbonyl organic electrode material containing naphthalene imide as claimed in claim 1, characterized in that: The electrode material is used for preparing the positive electrode of a metal ion battery.

6. The use of the polycarbonyl organic electrode material containing naphthalene imide as claimed in claim 5, characterized in that: The metal ion battery positive electrode is: a zinc ion battery positive electrode or a lithium ion battery positive electrode.

7. The use of the polycarbonyl organic electrode material containing naphthalene imide according to claim 6, characterized in that: Used to prepare the positive electrode of zinc ion battery, the current collector is graphite paper, and the electrolyte is 0.5-1.5M sulfuric acid, 3M zinc sulfate, and 0.3-2M zinc sulfonate.

8. The use of the polycarbonyl organic electrode material containing naphthalene imide as claimed in claim 6, characterized in that: Used to prepare the positive electrode of lithium-ion batteries, the current collector is aluminum foil, and the electrolyte is 1 mol / L lithium bis(trifluoromethylsulfonyl)imide.

Citation Information

Patent Citations

  • Lithium ion battery organic positive electrode material and application thereof

    CN110429279A

  • Naphtho [2, 3-d] imidazole-4, 9-diketone derivative used as positive electrode of organic lithium ion battery and preparation method of naphtho [2, 3-d] imidazole-4, 9-diketone derivative

    CN115710230A

  • Organic nano electrode material for sodium-ion battery as well as preparation method and application of organic nano electrode material

    CN116715665A

  • New Anti-clostridium compounds

    US20170035750A1

Cited By

  • Hydroxyl-containing multi-active-site quinone organic electrode material and application thereof in metal zinc ion battery

    CN120965598A

  • Positive electrode composite material, electrode, three-ion secondary battery and application of three-ion secondary battery

    CN121641928A